Relationship between serum ferritin and parathyroid function in adult male patients with transfusion dependent thalassemia - Urmi, SFH; Munira, Fatema Tuz; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2022)
Background: Thalassemia is a genetic disorder of defective hemoglobin synthesis. In transfusion dependent thalassemia (TDT), iron overload is caused by repeated blood transfusion for a long time. This increased iron is deposited in body tissue and may lead to endocrine dysfunction. Objective: To evaluate the relationship between serum ferritin and parathyroid dysfunction in adult male patients with TDT. Methods: It was a cross sectional study which was conducted from March 2018 to February 2019 in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. For this study, 35 TDT male patients aged 18 to 40 year, were considered as study group and 35 age and sex matched apparently healthy subjects were considered as control group. The outpatient department of Hematology and Transfusion Medicine was the point of collection of study group. Parathyroid function was assessed by plasma intact para thyroid hormone (iPTH), serum total calcium and serum inorganic phosphate. Plasma iPTH and serum ferritin levels were estimated by Electrochemiluminescence Immunoassay method using automated analyzer. Serum total calcium and serum inorganic phosphate levels were estimated by colorimetric method using automated analyzer. Independent sample t test and Pearson’s correlation coefficient (r) test were applied for statistical analysis using SPSS version 16. Results: In this study, serum ferritin level was significantly (p <0.001) higher in patients with TDT than that of healthy control. Correlation analysis showed negative correlation of serum ferritin with plasma iPTH and serum corrected calcium and positive correlation with serum inorganic phosphate in patients with TDT. Among them correlation with serum corrected calcium and inorganic phosphate were statistically significant (p <0.05). Conclusion: This study concluded that TDT may be associated with elevated iron status which is inversely related with parathyroid function. J Bangladesh Soc Physiol. 2022, June; 17(1): 1-5